Exploring the mechanisms of exciton diffusion improvement in ternary polymer solar cells: From ultrafast to ultraslow temporal scale. (January 2021) - Zhang, Kang-Ning; Jiang, Zhi-Nan; Wang, Tong; Qiao, Jia-Wei; Feng, Lin; Qin, Chao-Chao; Yin, Hang; So, Shu-Kong; Hao, Xiao-Tao
Abstract: Long-range exciton diffusion on picosecond time scale, which serves to efficient charge separation at the donor/acceptor (D/A) interfaces, has been regarded as a key step for the working mechanisms of organic photovoltaics. Rationally understanding and manipulating this vital process over a wide temporal scale remains some challenges, especially in ternary organic solar cells (OSCs). Herein, we reveal how exciton migration behaviors are reasonably improved and maintained relying on the simultaneously enhanced efficiency and thermal stability in the PM6:IT4F:PC71 BM and PM6:BTP-4Cl:PC71 BM ternary devices. Two separate factors can be responsible for these benefits: (1) the coexistence of dual Förster-type energy transfer (FRET) can contribute to the directed exciton diffusion and rapidly quench the highly excited states to stabilize the "energy donors". (2) The more favorable multi-length scale morphologies optimized by the addition of guest PC71 BM yield the plentiful interfacial region to shorten the real distance of diffusion process and boost the stability of microstructure. In particular, the diffusion lengths > 10 nm of IT4F singlet excitons induced by dual FRET effects were obtained by employing the exciton-exciton annihilation strategy. These experimental results open a novel horizon for further strengthening efficiency and stability of ternary OSCs from the perspective of improving exciton diffusion. Graphical Abstract: The improved exciton diffusion behaviors across a wide temporal scale have been obtained relying on the simultaneously enhanced efficiency and thermal stability in the PM6:IT4F:PC71 BM and PM6:BTP-4Cl:PC71 BM ternary organic solar cells. Two dominant separate working mechanisms are responsible for these benefits: (1) the coexistence of dual Förster resonance energy transfer (FRET) effects, and (2) the more favorable multi-length scale morphologies. ga1 Highlights: Effective exciton diffusion behaviors are obtained and well maintained across a wide temporal scale. Dual FRET effects contribute to the directed exciton diffusion in ternary blends. The diffusion lengths > 10 nm of IT4F singlet excitons are induced by dual FRET mechanisms. The optimized multi-length scale morphologies shorten the real distance of exciton reaching the interface region.